Metal- and solvent-free preparation of benzo[4,5]imidazo[1,2-a]pyrimidine derivatives catalysed by deep eutectic solvents - Thuy-Duy Thi Nguyen; Anh Vy Truong; Hoang Phuong Tran (Vietnam Journal of Science, Technology and Engineering, 2021)
Deep eutectic solvents (DESs) were first reported by Abbott and co-workers in 2001 and has since been widely applied to electrolytes, electrodeposition, electropolishing, ionothermal synthesis, gas adsorption, and biotransformation. DESs are classified as a new class of ionic liquids that present many outstanding characteristics such as low vapor pressure, nonflammability, easy preparation, low cost, and large recovery. DESs are classified as a new class of ionic liquids that present many outstanding characteristics such as low vapor pressure, nonflammability, easy preparation, low cost, and large recovery. These characteristics make DESs well-known as green solvents for organic transformations. These characteristics make DESs well-known as green solvents for organic transformations. The Biginelli reaction, first reported in 1891, played an important role in the synthesis of pyrimidine derivatives. A straightforward method for the preparation of benzo[4,5]imidazo[1,2-a]pyrimidine derivatives catalysed by an acidic deep eutectic solvent from choline chloride (ChCl) and phenol via the Biginelli reaction of 2-aminobenzimidazole, ethyl acetoacetate, and aldehydes has been developed under metal- and solvent-free conditions. The desired products were obtained in moderate to good yield (49-79%) and the DESs were known as an economical and environmentally friendly catalyst.